PENGARUH METODE INDEX CARD MATCH TERHADAP KETERAMPILAN MEMBACA SISWA KELAS II SD NEGERI 2 TIJUE - Nanda Saputra; Arizal Fahmi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The problem in this study was there were a lot of students at SDN 2 Tijue who had low competence in reading skill. The fact indicated that there were still many students who spell, could not distinguish letters, adding the word and reducing word. This study aims to determine the effect of reading skills by using the index card match method for second grade students at SDN 2 Tijue, Pidie District. The population in this study were all students of second grade at SDN 2 Tijue. The number of the students were 50 while the samples in this study were class II as many as 50 students. The result of the study showed t count > t table. The result was 2,655 > 1,711 and df 48. It showed that there was an effect of the index card match method on reading skills of at second grade students in Pidie District